Application Of Practicum-Based Project Based Learning To Improve Science Literacy And Student Participation In Elementary School: A Pre-Experimental Study on Ecosystem Learning in Grade V Students - Nurlena Andalia; Sri Ardiani; Evi Apriana; Ibrahim Ibrahim; Masyudi Masyudi (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
Science learning in elementary schools is often dominated by conventional methods, resulting in low science literacy and limited student participation. This study aims to examine the effectiveness of practicum-based Project Based Learning in improving science literacy and student participation. A quantitative approach with a one-group pretest–posttest design was employed involving 34 fifth-grade students. Data were collected through science literacy tests and observation sheets of student participation. The results showed a significant improvement in students’ science literacy, with the average score increasing from 68.41 to 86.76 and an N-Gain score of 0.58, categorized as moderate. In addition, student participation improved as reflected in increased engagement during discussions, experiments, and project activities. These findings indicate that practicum-based Project Based Learning provides meaningful learning experiences and effectively enhances both science literacy and student participation.